Wordplay on proper names in Luke-Acts - Reece, Steve (Novum Testamentum / Supplements, 2026)
"This monograph identifies forty proper names in Luke-Acts whose meanings are significant in their narrative contexts. About half of these names are also used in various types of verbal wordplays. Is the name of the recipient of both of Luke's works, Theophilus "Loved by God," used meaningfully? Is the name of Eutychus "Fortunate," who survives a fall from a third-story window, significant in the context of this story? Does the common appearance of the name Rhoda "Rose" in New Comedy contribute a comical element to her role as an ineffective door keeper? Luke's literary practice in his treatment of names appears to be fundamentally different from that of other New Testament writers. Why is this the case?"-- Provided by publisher